2021
DOI: 10.1200/op.20.00839
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Refusal of Locoregional Treatment for Prostate Adenocarcinoma

Abstract: PURPOSE: We assessed sociodemographic factors associated with and survival implications of refusal of potentially survival-prolonging locoregional treatment (LT, including radiotherapy and surgery) despite provider recommendation among men with localized prostate adenocarcinoma. METHODS: The National Cancer Database (2004-2015) identified men with TxN0M0 prostate cancer who either received or refused LT despite provider recommendation. Multivariable logistic regression defined adjusted odds ratios (AORs) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…In addition, we identified that API patient was also a population with high odds of refusing recommended surgery. A latest study by Dee et al ( 13 ) found that black and Asian patients are more likely to refuse locoregional treatment (radiotherapy and surgery) than white patients in prostate cancer; locoregional treatment refusal rate for prostate adenocarcinoma has increased over time. For Lung/bronchus cancer patients, Mehta et al ( 14 ) found that blacks and “other” races are more likely to refuse recommended surgery than whites; refusal of surgery is influenced by county variations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we identified that API patient was also a population with high odds of refusing recommended surgery. A latest study by Dee et al ( 13 ) found that black and Asian patients are more likely to refuse locoregional treatment (radiotherapy and surgery) than white patients in prostate cancer; locoregional treatment refusal rate for prostate adenocarcinoma has increased over time. For Lung/bronchus cancer patients, Mehta et al ( 14 ) found that blacks and “other” races are more likely to refuse recommended surgery than whites; refusal of surgery is influenced by county variations.…”
Section: Discussionmentioning
confidence: 99%
“…Mistrust of the medical institution resulting from historical injustices as well as prior direct interactions may lead to avoidance of the health care system until symptoms are progressed, 65 with consequent delays in cancer diagnosis and treatment. Racial differences in rates of mistrust toward the medical system persist among people with cancer, 66 likely affecting not just rates of screening but also the decision to adhere to treatment recommendations 41, 44 . Although the medical system has made efforts to protect marginalized populations given these difficult prior lessons, injustices persist, and consequent mistrust may understandably still linger.…”
Section: Conflict Of Interest Disclosuresmentioning
confidence: 99%
“…It is important to note that although the work of Snyder et al 33 does not explicitly examine cancer outcomes (indeed, the National Cancer Database reports only overall survival and not cancer-specific outcomes), disparities in stage at presentation may only represent the "tip of the iceberg"; disparities in treatment and the survivorship setting after diagnosis lead to more disparate cancer outcomes. [40][41][42][43][44][45] The persistence of cancer disparities despite interventions aimed at improving access to care highlight that despite Cancer September 15, 2022 improvements in insurance coverage, there are other factors at play that mediate cancer disparities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] Despite these advances in radiotherapy techniques, inequities in their utilization and subsequent disparities in oncologic outcomes persist for Black versus non-Black patients with BC and PC in the United States. [22][23][24][25][26] This is attributable in part to systemic bias and barriers in access to care. 27 One important potential benefit of shorter fractionation schemes is an improvement in treatment completion rates among patients receiving radiation therapy (RT).…”
Section: Corresponding Author Introductionmentioning
confidence: 99%